Understanding the Effects of Climate Change on the 'Jangal Mahal' Forest Regions in West Bengal, India (International Journal of Innovative Research in Engineering & Management, 2024)
Against the backdrop of growing global  climate concerns, this study attempts to comprehensively  explore the impacts of climate change in the Jangal  Mahal forest region of West Bengal, India through the  perception of forest dependent communities. In this  context, we have attempted to address climate change  perceptions regarding impacts on forest ecosystems  through descriptive statistics. We used primary data  collected randomly from 241 households in 8 blocks of  Jangal Mahal region of West Bengal. Data collection in  this study was through questionnaire based personal in depth interviews. We selected 10 indicators to measure  household perceptions of climate change and the impacts  of climate change on forests. The results show that  households strongly agree with the increase in average  temperature, increase in hot days, unpredictability of  rainfall and climate change events but strongly disagree  with changes in withdrawal of monsoon, longer winter  season and increase in rainfall. It has also been observed  that climate change is having severe negative impact on  Non-timber forest product (NTFP) quality, soil fertility,  wood supply, mortality of native plant species and forest  density, but no serious impact on forest biological  systems.
Keywords: Climate Change; Forest; Jungal Mahal